Pengaruh Citra Merek, Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Produk 3 Second Kota Malang (Studi Kasus Pada Mahasiswa UNISMA) - Sindi Puji Lestari; Rois Arifin; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study aims to determine the effect of brand image, product quality and price on product purchasing decisions 3Second Malang City. The location of this research was carried out on UNISMA students who became consumers of 3Second Malang City. This research is a quantitative research. This research uses a case study method where data is obtained by distributing questionnaires to UNISMA students who were selected by purposive sampling. Determination of the number of samples using the Maholtra formula and the results obtained were 75 respondents. Data were analyzed using multiple linear regression test and determination test. Based on the results of data analysis, the results of the F test indicate that brand image, product quality and price have a significant and positive effect on purchasing decisions and affect purchasing decisions for 3Second products in Malang City. Furthermore, the results of the t-test indicate that brand image, product quality and price partially have a significant and positive effect on purchasing decisions for 3Second products in Malang City. The results of the determination test show that the percentage is 69.1%, which is where purchasing decisions can be influenced by brand image, product quality and price. Management should pay more attention to consumer attitudes and behavior in the purchase stage, one of which is by providing good quality products so that consumers will easily buy 3Second products more precisely and quickly. Keywords: Purchase Decision, Brand Image, Product Quality, Price